2014
DOI: 10.1177/1541204013519828
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Gang Involvement in a Justice-Referred Sample of Youth in Treatment

Abstract: Gangs are present in about 34% of all jurisdictions in the United States. Given elevations in violence and victimization associated with gang involvement, effective means are needed for measuring involvement among individual youth. This is especially the case among youth receiving services for problem behavior who might benefit from targeted treatments helping them reduce involvement in gangs. We assessed gang involvement among 421 youth referred by the justice system for intensive home-and community-based men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The project, however, has been difficult to start because of the lack of engagement of gang-involved youth and their families (see http://www.ccjs.umd.edu/projectprofile/823). Research on another proven violence-reduction program, Multisystemic Therapy (MST), has shown that youth who were self-identified gang members displayed more risk factors and were more likely to drop out of the MST treatment than those who were not gang members (Boxer et al, 2015). These findings reinforce the importance of engagement and relationship building (Chablani & Spinney, 2011) throughout the process of intervening with high-risk classes of youth.…”
Section: Interventions With Gangs and Crewsmentioning
confidence: 96%
See 2 more Smart Citations
“…The project, however, has been difficult to start because of the lack of engagement of gang-involved youth and their families (see http://www.ccjs.umd.edu/projectprofile/823). Research on another proven violence-reduction program, Multisystemic Therapy (MST), has shown that youth who were self-identified gang members displayed more risk factors and were more likely to drop out of the MST treatment than those who were not gang members (Boxer et al, 2015). These findings reinforce the importance of engagement and relationship building (Chablani & Spinney, 2011) throughout the process of intervening with high-risk classes of youth.…”
Section: Interventions With Gangs and Crewsmentioning
confidence: 96%
“…Service providers had to go into the field to make those connections and provide treatment in the streets in order for the young parents to receive the level of necessary treatment support services to be successful. Other research reinforces the problems with providing services to these youth (Boxer et al, 2015). One proven violence-reduction program, Functional Family Therapy, is being tested on gang members in Pennsylvania.…”
Section: Interventions With Gangs and Crewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant associations with expected variables (and in the expected direction) are taken as evidence of the validity of the measure of gang membership (e.g., Thornberry et al, 2003;Matsuda et al 2012;Boxer et al, 2015). Cronbach and Meehl (1955) designated this strategy as the construction of 'nomological networks', with Cronbach (1988) subsequently distinguishing between 'strong' (theoretically articulated) and 'weak' (empirically sought) networks.…”
Section: Table 3 About Herementioning
confidence: 99%
“…associated with other variables of theoretical significance (e.g., Thornberry et al 2003;Boxer et al 2015). They have also made arguments for criterion validity, pointing to the overlap between selfreports of gang membership and the police's identification of gang members (Curry 2000).…”
Section: Introductionmentioning
confidence: 99%